Prevalence and risk factors of persistent stress urinary incontinence at three months postpartum in Indonesian women (Medical Journal of Indonesia, 2016)
Background: Mode of delivery and some certain risk factors have a relationship to postpartum stress urinary incontinence (SUI). For that reason, the objective of this study was to assess the prevalence of postpartum stress urinary incontinence (SUI), the relationship between postpartum SUI and mode of delivery; and the association between SUI and other demographic and obstetric factors.Methods: In this prospective observational cohort study, all primiparous women who were under postpartum care in obstetric and gynecologic ward were recruited. Four hundreds primiparous women with no history of urinary incontinence (UI) who fulfilled the criteria and would like to participate in this study were followed up for three months after delivery. The analysis was done using Stata 12. Bivariate analysis using Chi-square test and multivariate analysis using logistic regression test were done to obtain associated risk factors to postpartum SUI.Results: The prevalence of postpartum SUI was 8.8%. The mode of delivery was significantly associated with postpartum SUI, there were more women who got vaginal delivery that had stress urinary incontinence (14.1%) compared to women caesarean section (7.1%) with OR=2.1 (95% CI=1.05-4.31), this risk increased when vaginal delivery was assisted with vacuum instrument (OR=9.1, 95% CI=3.9-21.6). There was no statistical difference of stress urinary incontinence incidences in patients with emergency or elective caesarean section with OR=0.84 (95% CI=0.28-2.57). Based on multivariate analysis BMI â¥30 kg/m2 at labor, vacuum assisted delivery, birth weight more than 3,360 g, and second stage labor more than 60 minutes appeared to be associated with an increased rate of postpartum SUI.Conclusion: Stress urinary incontinence increased in the early postpartum period of a primiparous woman. Although vaginal delivery increased the risk of postpartum SUI, elective nor emergency caesarean delivery without vaginal delivery id not appear to increase the risk of stress urinary incontinence.